2020
DOI: 10.3389/fpsyt.2020.599039
|View full text |Cite
|
Sign up to set email alerts
|

Masculinity and Help-Seeking Among Men With Depression: A Qualitative Study

Abstract: Background: Many studies indicate that men are more reluctant to seek help for mental health problems than women. Traditional ideas of masculinity are often seen as a cause of this phenomenon. However, little is known about the diversity of experiences during the processes of help-seeking and service use among men with depression who have already utilized mental health services. This study aims to explore men's experiences and attitudes toward depression, help-seeking, and service use in order to develop gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 29 publications
3
60
1
3
Order By: Relevance
“…Six studies reported how mental illness stigma and men's fear of transgressing masculine cultures normed by strength, independence, and invincibility, can play out in male-dominated environments such as places of paid work and professional sport (DeLenardo & Terrion, 2014;Hassouneh & Fornero, 2020;Mahalik & Dagirmanjian, 2019;Siegel & Sawyer, 2019;Staiger et al, 2020;Wood et al, 2017). Consistently reported by men in these studies was the fear of being perceived as weak, incapable of coping with distress, and failing to fulfill the masculine norms deemed mandatory for specific male dominated jobs and sports.…”
Section: Stigma In Male-dominated Environmentsmentioning
confidence: 93%
See 4 more Smart Citations
“…Six studies reported how mental illness stigma and men's fear of transgressing masculine cultures normed by strength, independence, and invincibility, can play out in male-dominated environments such as places of paid work and professional sport (DeLenardo & Terrion, 2014;Hassouneh & Fornero, 2020;Mahalik & Dagirmanjian, 2019;Siegel & Sawyer, 2019;Staiger et al, 2020;Wood et al, 2017). Consistently reported by men in these studies was the fear of being perceived as weak, incapable of coping with distress, and failing to fulfill the masculine norms deemed mandatory for specific male dominated jobs and sports.…”
Section: Stigma In Male-dominated Environmentsmentioning
confidence: 93%
“…The stigma of EDs was seen as more stigmatizing and shameful for men given Eds are typically viewed as a feminine disorder. Staiger et al (2020), Germany To explore men's experiences and attitudes toward depression, helpseeking, and service use None Semi-structured interviews 12 men diagnosed or selfidentified as having depression (age 16-64) Men described feeling stigmatized and, in some cases, shunned by work colleagues for not being unable to cope with mental distress, and for failing to meet the norms relating to paid work. Men's depression-related incapacity to work and being labeled left them feeling further stigmatized.…”
Section: Nonementioning
confidence: 99%
See 3 more Smart Citations